ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN KLUNGKUNG PROVINSI BALI - Lutvi Niswa Octaviana (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The goal of the study is to determine whether economic development and poverty levels in Bali Province's Klungkung Regency have an impact on the human development index. Economic growth and poverty level are the two independent variables in this descriptive quantitative research design. The Central Statistics Agency (BPS) of Bali Province and Klungkung Regency provided samples and data sources for this study, which employed time series data from 2007 to 2021. After being collected for this study, the data were subsequently subjected to double linear regression analysis. Researchers came to the conclusion that the Human Development Index in Klungkung Regency is significantly impacted by both economic growth and poverty.